Carbon-bonded alumina foam filters produced by centrifugation: A route towards improved homogeneity. Issue 12 (15th August 2018) - Luchini, B.; Hubálková, J.; Wetzig, T.; Grabenhorst, J.; Fruhstorfer, J.; Pandolfelli, V.C.; Aneziris, C.G.
Abstract: An alternative route for producing carbon-bonded alumina filters was analyzed and compared with the state of the art, both based on the replica method. The latter comprises a dip coating and subsequent rolling and spraying steps ( R+S ). The proposed route is based on dip coating and centrifugation ( CF-T1 ). Aiming to investigate the influence of an additional thermal treatment on the ceramic coating homogeneity, a modified centrifugation route was analyzed ( CF-T2 ). Computer tomography (CT) analyses provided a targeted evaluation of the spatial material distribution after each processing step. It was found that log-normal functions fitted well the wall thickness values attained for all investigated filters. Qualitative surface evaluation was conducted using a digital (optical) microscope. The R+S and CF-T1 filters exhibited surface macro-cracks and hollow struts, due to the release of the polyurethane foam template during firing. The CF-T2 presented partly filled struts with a high amount of micro-cracks on the surface, being a potential alternative to increase the filtration efficiency, as the filter surface area was raised. However, in preliminary mechanical tests, the surface micro-cracks seemed to considerably reduce the cold crushing strength of the CF-T2 filters. Based on the CT data, it was possible to conclude that the centrifuged filters presented a more homogeneous material distribution, as a consequence of higher automation level of the process.